High-temperature-resistant PVC tile and preparation method thereof
By organically grafting illite and loading it with carbon chlorinated nanotubes as a reinforcing agent, the compatibility and dispersion of fillers with the matrix of PVC tiles were improved, solving the problem of rapid aging of PVC tiles at high temperatures and achieving improved mechanical strength under high-temperature conditions.
Patent Information
- Application Number
- CN202511316736.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-16
- Publication Date
- 2025-12-02
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing PVC roofing sheets age rapidly under high temperatures and lack sufficient mechanical strength, limiting their application in high-temperature regions.
An organic grafting process using illite and loading of acyl chloride carbon nanotubes as a reinforcing agent improves the compatibility and dispersion of the filler with the matrix and enhances the bonding strength of the material through a unique formulation and preparation process.
It significantly improves the thermal stability and mechanical strength of PVC tiles, enabling them to maintain good mechanical properties even with high filler content and resist the effects of high-temperature aging.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of PVC material technology, specifically relating to a high-temperature resistant PVC tile and its preparation method. Background Technology
[0002] PVC roofing sheets are widely used in the construction industry due to their advantages such as light weight, easy installation, and low cost. In existing manufacturing methods, calcium carbonate is a commonly used filler for PVC synthetic resin roofing sheets, which can reduce costs and provide some mechanical reinforcement. However, when its content is high, the poor compatibility between calcium carbonate and the polymer matrix results in limited dispersion, affecting the material's mechanical strength. Furthermore, PVC roofing sheets have poor high-temperature resistance; when used outdoors, prolonged exposure to high temperatures and sunlight can easily lead to aging and insufficient mechanical strength, significantly reducing product lifespan and safety. This limits the application of PVC roofing sheets in high-temperature regions or special building scenarios with high temperature requirements. Summary of the Invention
[0003] To address the problems existing in the background technology, the present invention provides a high-temperature resistant PVC tile and its preparation method. Through a unique formula and preparation process, the thermal stability of the PVC tile can be significantly improved, effectively resisting the influence of high temperature on the material properties. At the same time, it enhances the bonding force between the filler and the matrix, improves the uniform dispersion ability between materials, and ensures that the material has high mechanical strength under high filler content.
[0004] A high-temperature resistant PVC tile is prepared from the following raw material components: 100 parts PVC resin, 35-45 parts calcium carbonate, 14-16 parts reinforcing agent, 2-3 parts plasticizer, 1-3 parts crosslinking agent, 0.5-1.5 parts carbon black, 0.5-2 parts zinc oxide and 0.4-0.6 parts antioxidant;
[0005] The reinforcing agent is obtained by organic grafting illite and then loading it with carbon chloride nanotubes.
[0006] Furthermore, the method for preparing the reinforcing agent includes the following:
[0007] A1. Add illite to an alkaline solution for pretreatment, then add the pretreated illite to a dichloromethane solution containing a silane coupling agent and stir at room temperature for 2-3 hours to obtain an activated illite solution;
[0008] A2. Add 4-6 parts of carboxylated polyethylene glycol and 0.3-0.8 parts of sodium cyanoborohydrogenate to 100 parts of illite activation solution, adjust the pH to 2-3, stir evenly, heat to 60-80℃, stir and react for 4-6 hours, then add 0.8-1.2 parts of acyl chloride carbon nanotubes, continue stirring for 2-4 hours. After the reaction is complete, filter and dry to obtain the reinforcing agent.
[0009] Further, the pretreatment process in step A1 includes the following: adding illite to an alkaline solution with a mass fraction of 50-70%, stirring at room temperature for 4-6 hours, filtering, washing with water, and drying to obtain pretreated illite.
[0010] Furthermore, in step A1, the mass fraction of the silane coupling agent in the dichloromethane solution is 0.1-0.5%, and the mass ratio of the pretreated illite to the dichloromethane solution is 1:8-12.
[0011] Further, the preparation method of acyl chloride carbon nanotubes in step A2 includes the following: carboxylating carbon nanotubes, then mixing 1 part of carboxylated carbon nanotubes with 8-12 parts of thionyl chloride, heating to 60-80℃, stirring and reacting for 3-10 hours, filtering, washing and drying to obtain the acyl chloride carbon nanotubes.
[0012] Furthermore, the plasticizer is one or a mixture of two of diethyl phthalate and dibutyl phthalate.
[0013] Furthermore, the illite has a particle size range of 800-1500 mesh.
[0014] Furthermore, the crosslinking agent is a mixture of diethylpropylbenzene peroxide and triallyl isocyanurate in a mass ratio of 2:1.
[0015] Furthermore, the antioxidant is one or a mixture of antioxidant 1010 and antioxidant 168.
[0016] A method for preparing PVC roofing sheets, used to prepare the high-temperature resistant PVC roofing sheets described in the above scheme, includes the following steps:
[0017] 1. Weigh each raw material component according to the weight parts, mix the reinforcing agent and calcium carbonate evenly to obtain the pre-doped filler;
[0018] 2. The pre-doped filler and other raw materials are transferred to an extruder and heated and extruded to obtain PVC plasticized sheets;
[0019] 3. PVC plasticized sheets are heated and shaped in a mold, cooled, and cut to obtain PVC tiles.
[0020] This application has the following beneficial effects:
[0021] 1. This invention provides a high-temperature resistant PVC tile and its preparation method. Through a unique combination of raw materials and preparation process, the thermal stability of the PVC tile is significantly improved, which can effectively resist the influence of high-temperature aging on the mechanical strength of the material. At the same time, it improves the dispersion uniformity of the filler, enhances the bonding force between the filler and the matrix, and ensures that the material can still have good mechanical strength under high filler content.
[0022] 2. In the preparation of reinforcing agents, illite is a layered silicate mineral with high dimensional stability, which can improve the processing performance and anti-aging performance of PVC. By modifying it and introducing polyethylene glycol and acyl chloride carbon nanotubes respectively, the dispersibility of fillers and compatibility with polymer matrix can be improved, enabling the material to form a stable microstructure during molding, thereby improving high temperature aging resistance and mechanical strength.
[0023] 3. Organic grafting of illite with polyethylene glycol, followed by pre-doping with reinforcing agents and calcium carbonate, effectively improves the compatibility between illite, calcium carbonate, and the PVC resin matrix. Loading highly reactive acyl chloride carbon nanotubes enhances the bonding between the carbon nanotubes and illite. Furthermore, the carbon nanotubes extend onto the layered surface of illite, increasing its roughness and specific surface area, significantly improving its mechanical reinforcement. The acyl chloride treatment of the carbon nanotubes also enhances their reactivity, allowing them to interact and attract with the grafted polyethylene glycol, forming a stable three-dimensional structure combining organic and inorganic components on the layered illite surface. This facilitates good intercalation between the reinforcing agent and the polymer matrix, further improving the material's resistance to high-temperature aging. Detailed Implementation
[0024] The present application will be further described in detail below with reference to the embodiments.
[0025] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.
[0026] Example 1
[0027] A method for preparing PVC roofing sheets includes the following steps:
[0028] 1. Weigh each raw material according to the following parts by weight, specifically including the following components: 100 parts PVC resin, 40 parts calcium carbonate, 15 parts reinforcing agent, 2.5 parts plasticizer, 2 parts crosslinking agent, 1 part carbon black, 1 part zinc oxide and 0.5 parts antioxidant. Mix the reinforcing agent and calcium carbonate evenly to obtain the pre-doped filler.
[0029] The plasticizer is diethyl phthalate, the calcium carbonate has a particle size of 1000 mesh, the crosslinking agent is a mixture of diethyl propylene peroxide and triallyl isocyanurate in a mass ratio of 2:1, and the antioxidant is antioxidant 1010.
[0030] 2. The pre-doped filler and other raw materials are transferred to an extruder and heated for extrusion, wherein the extrusion die temperature range is 180-190℃, to obtain PVC plasticized sheets;
[0031] 3. PVC plasticized sheets are heated and shaped in a mold, cooled, and cut to obtain PVC tiles.
[0032] The preparation method of the reinforcing agent includes the following:
[0033] A1. Illite with a particle size of 1000 mesh was added to an alkaline solution with a mass fraction of 60%, stirred at room temperature for 5 hours, filtered, washed with water, and dried to obtain pretreated illite. Then, the pretreated illite was added to a dichloromethane solution containing a silane coupling agent and stirred at room temperature for 2.5 hours to obtain an illite activation solution. The dichloromethane solution included dichloromethane and the silane coupling agent KH560, with a mass fraction of 0.3% for the silane coupling agent. The mass ratio of pretreated illite to dichloromethane solution was 1:10.
[0034] A2. Add 5 parts of carboxylated polyethylene glycol and 0.5 parts of sodium cyanoborohydrogenate to 100 parts of illite activation solution, adjust the pH to 2-3, stir evenly, heat to 70℃, stir and react for 5 hours, then add 1 part of acyl chloride carbon nanotubes, continue stirring for 3 hours, after the reaction is completed, filter and dry to obtain the reinforcing agent.
[0035] The preparation method of acyl chloride carbon nanotubes in step A2 includes the following: carboxylating carbon nanotubes, then mixing 1 part of carboxylated carbon nanotubes with 10 parts of thionyl chloride, heating to 70°C, stirring and reacting for 5 hours, filtering, washing and drying to obtain the acyl chloride carbon nanotubes.
[0036] Example 2
[0037] A method for preparing PVC roofing sheets includes the following steps:
[0038] 1. Weigh each raw material according to the following parts by weight, specifically including the following components: 100 parts PVC resin, 45 parts calcium carbonate, 14 parts reinforcing agent, 3 parts plasticizer, 1 part crosslinking agent, 0.5 parts carbon black, 0.5 parts zinc oxide and 0.4 parts antioxidant. Mix the reinforcing agent and calcium carbonate evenly to obtain the pre-doped filler.
[0039] The plasticizer is dibutyl phthalate, the calcium carbonate has a particle size of 800 mesh, the crosslinking agent is a mixture of diethylpropylbenzene peroxide and triallyl isocyanurate in a mass ratio of 2:1, and the antioxidant is antioxidant 168.
[0040] 2. The pre-doped filler and other raw materials are transferred to an extruder and heated for extrusion, wherein the extrusion die temperature range is 180-190℃, to obtain PVC plasticized sheets;
[0041] 3. PVC plasticized sheets are heated and shaped in a mold, cooled, and cut to obtain PVC tiles.
[0042] The preparation method of the reinforcing agent includes the following:
[0043] A1. Illite with a particle size of 800 mesh was added to a 50% alkaline solution and stirred at room temperature for 6 hours. The mixture was then filtered, washed with water, and dried to obtain pretreated illite. The pretreated illite was then added to a dichloromethane solution containing a silane coupling agent and stirred at room temperature for 2 hours to obtain an activated illite solution. The dichloromethane solution contained dichloromethane and the silane coupling agent KH560, with a mass fraction of 0.5% for the silane coupling agent. The mass ratio of pretreated illite to dichloromethane solution was 1:8.
[0044] A2. Add 4 parts of carboxylated polyethylene glycol and 0.3 parts of sodium cyanoborohydrate to 100 parts of illite activation solution, adjust the pH to 2-3, stir evenly, heat to 60℃, stir and react for 6 hours, then add 0.8 parts of acyl chloride carbon nanotubes, continue stirring for 4 hours, after the reaction is completed, filter and dry to obtain the reinforcing agent.
[0045] The preparation method of acyl chloride carbon nanotubes in step A2 includes the following: carboxylating carbon nanotubes, then mixing 1 part of carboxylated carbon nanotubes with 8 parts of thionyl chloride, heating to 60°C, stirring and reacting for 10 h, filtering, washing and drying to obtain the acyl chloride carbon nanotubes.
[0046] Example 3
[0047] A method for preparing PVC roofing sheets includes the following steps:
[0048] 1. Weigh each raw material according to the following parts by weight, specifically including the following components: 100 parts PVC resin, 35 parts calcium carbonate, 16 parts reinforcing agent, 2 parts plasticizer, 3 parts crosslinking agent, 1.5 parts carbon black, 2 parts zinc oxide and 0.6 parts antioxidant. Mix the reinforcing agent and calcium carbonate evenly to obtain the pre-doped filler.
[0049] The plasticizer is diethyl phthalate, the calcium carbonate has a particle size of 1500 mesh, the crosslinking agent is a mixture of diethylpropylbenzene peroxide and triallyl isocyanurate in a mass ratio of 2:1, and the antioxidant is antioxidant 168.
[0050] 2. The pre-doped filler and other raw materials are transferred to an extruder and heated for extrusion, wherein the extrusion die temperature range is 180-190℃, to obtain PVC plasticized sheets;
[0051] 3. PVC plasticized sheets are heated and shaped in a mold, cooled, and cut to obtain PVC tiles.
[0052] The preparation method of the reinforcing agent includes the following:
[0053] A1. Illite with a particle size of 1500 mesh was added to an alkaline solution with a mass fraction of 70%, stirred at room temperature for 4 hours, filtered, washed with water, and dried to obtain pretreated illite. Then, the pretreated illite was added to a dichloromethane solution containing a silane coupling agent and stirred at room temperature for 3 hours to obtain an illite activation solution. The dichloromethane solution included dichloromethane and the silane coupling agent KH560, with a mass fraction of 0.1% for the silane coupling agent. The mass ratio of pretreated illite to dichloromethane solution was 1:12.
[0054] A2. Add 6 parts of carboxylated polyethylene glycol and 0.8 parts of sodium cyanoborohydrate to 100 parts of illite activation solution, adjust the pH to 2-3, stir evenly, heat to 80℃, stir and react for 4 hours, then add 1.2 parts of acyl chloride carbon nanotubes, continue stirring for 3 hours, after the reaction is completed, filter and dry to obtain the reinforcing agent.
[0055] The preparation method of acyl chloride carbon nanotubes in step A2 includes the following: carboxylating carbon nanotubes, then mixing 1 part of carboxylated carbon nanotubes with 12 parts of thionyl chloride, heating to 80°C, stirring and reacting for 3 hours, filtering, washing and drying to obtain the acyl chloride carbon nanotubes.
[0056] Comparative Example 1
[0057] The only difference between this comparative example and Example 1 is that, in the preparation of the reinforcing agent, the carbon nanotubes were not subjected to acyl chloride treatment; that is, the acyl chloride carbon nanotubes were replaced with carbon nanotubes, as detailed below:
[0058] The preparation method of the reinforcing agent includes the following:
[0059] A1. Illite with a particle size of 1000 mesh was added to an alkaline solution with a mass fraction of 60%, stirred at room temperature for 5 hours, filtered, washed with water, and dried to obtain pretreated illite. Then, the pretreated illite was added to a dichloromethane solution containing a silane coupling agent and stirred at room temperature for 2.5 hours to obtain an illite activation solution. The dichloromethane solution included dichloromethane and the silane coupling agent KH560, with a mass fraction of 0.3% for the silane coupling agent. The mass ratio of pretreated illite to dichloromethane solution was 1:10.
[0060] A2. Add 5 parts of carboxylated polyethylene glycol and 0.5 parts of sodium cyanoborohydrate to 100 parts of illite activation solution, adjust the pH to 2-3, stir evenly, heat to 70℃, stir and react for 5 hours, then add 1 part of carbon nanotubes, continue stirring for 3 hours, after the reaction is completed, filter and dry to obtain the reinforcing agent.
[0061] Comparative Example 2
[0062] The only difference between this comparative example and Example 1 is that, in the preparation of the reinforcing agent, illite was not grafted with polyethylene glycol, as detailed below:
[0063] The preparation method of the reinforcing agent includes the following:
[0064] A1. Illite with a particle size of 1000 mesh was added to an alkaline solution with a mass fraction of 60%, stirred at room temperature for 5 hours, filtered, washed with water, and dried to obtain pretreated illite. Then, the pretreated illite was added to a dichloromethane solution containing a silane coupling agent and stirred at room temperature for 2.5 hours to obtain an illite activation solution. The dichloromethane solution included dichloromethane and the silane coupling agent KH560, with a mass fraction of 0.3% for the silane coupling agent. The mass ratio of pretreated illite to dichloromethane solution was 1:10.
[0065] A2. Add 0.5 parts sodium cyanoboronate to 100 parts illite activation solution, adjust the pH to 2-3, stir evenly, heat to 70℃, stir and react for 5 hours, then add 1 part acyl chloride carbon nanotubes, continue stirring for 3 hours, after the reaction is completed, filter and dry to obtain the reinforcing agent.
[0066] The preparation method of acyl chloride carbon nanotubes in step A2 includes the following: carboxylating carbon nanotubes, then mixing 1 part of carboxylated carbon nanotubes with 10 parts of thionyl chloride, heating to 70°C, stirring and reacting for 5 hours, filtering, washing and drying to obtain the acyl chloride carbon nanotubes.
[0067] Comparative Example 3
[0068] The only difference between this comparative example and Example 1 is that, in the preparation of the reinforcing agent, the carbon nanotubes were not subjected to acyl chloride treatment, and the illite was not grafted with polyethylene glycol.
[0069] Proof of effectiveness
[0070] The PVC materials obtained in Examples 1-3 and Comparative Examples 1-3 were used to prepare test samples, and their mechanical strength and high-temperature aging resistance were tested. The specific test results are shown in Table 1.
[0071] Tensile strength: The tensile strength of the specimen was determined according to GB / T 1040.2-2006 standard at a test speed of 50 mm / min.
[0072] High-temperature aging resistance: The tensile strength retention rate after treatment was tested by aging under a xenon lamp at 70°C for 7 days.
[0073] Table 1
[0074] Tensile strength / MPa High temperature aging resistance / % Example 1 48.3 92.4 Example 2 47.6 91.6 Example 3 48.1 92.1 Comparative Example 1 45.6 83.6 Comparative Example 2 43.8 86.2 Comparative Example 3 41.6 80.1
[0075] Results Analysis
[0076] Analysis of Examples 1-3 and Comparative Examples 1-3, and in conjunction with the data in Table 1, shows that the high-temperature resistant PVC material provided by the present invention (Examples 1-3) has a tensile strength of over 47.6 MPa and a high-temperature aging resistance of over 91.6%, which is significantly greater than that of Comparative Examples 1-3. Therefore, the high-temperature resistant PVC tile prepared by the present invention has high mechanical strength and thermal stability, can resist the influence of high-temperature aging on the mechanical strength of the material, and effectively improves the durability of the material.
[0077] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0078] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A high-temperature resistant PVC tile, characterized in that, It is prepared from the following raw material components: 100 parts PVC resin, 35-45 parts calcium carbonate, 14-16 parts reinforcing agent, 2-3 parts plasticizer, 1-3 parts crosslinking agent, 0.5-1.5 parts carbon black, 0.5-2 parts zinc oxide and 0.4-0.6 parts antioxidant; The reinforcing agent is obtained by organic grafting illite and then loading it with carbon chloride nanotubes.
2. The high-temperature resistant PVC tile according to claim 1, characterized in that, The preparation method of the reinforcing agent includes the following: A1. Add illite to an alkaline solution for pretreatment, then add the pretreated illite to a dichloromethane solution containing a silane coupling agent and stir at room temperature for 2-3 hours to obtain an activated illite solution; A2. Add 4-6 parts of carboxylated polyethylene glycol and 0.3-0.8 parts of sodium cyanoborohydrogenate to 100 parts of illite activation solution, adjust the pH to 2-3, stir evenly, heat to 60-80℃, stir and react for 4-6 hours, then add 0.8-1.2 parts of acyl chloride carbon nanotubes, continue stirring for 2-4 hours. After the reaction is complete, filter and dry to obtain the reinforcing agent.
3. The high-temperature resistant PVC tile according to claim 2, characterized in that, The pretreatment process in step A1 includes the following: adding illite to an alkaline solution with a mass fraction of 50-70%, stirring at room temperature for 4-6 hours, filtering, washing with water, and drying to obtain pretreated illite.
4. The high-temperature resistant PVC tile according to claim 2, characterized in that, In step A1, the mass fraction of silane coupling agent in the dichloromethane solution is 0.1-0.5%, and the mass ratio of pretreated illite to dichloromethane solution is 1:8-12.
5. The high-temperature resistant PVC tile according to claim 2, characterized in that, The preparation method of acyl chloride carbon nanotubes in step A2 includes the following: carboxylating carbon nanotubes, then mixing 1 part of carboxylated carbon nanotubes with 8-12 parts of thionyl chloride, heating to 60-80℃, stirring and reacting for 3-10 hours, filtering, washing and drying to obtain the acyl chloride carbon nanotubes.
6. The high-temperature resistant PVC tile according to claim 1, characterized in that, The plasticizer is one or a mixture of two of diethyl phthalate and dibutyl phthalate.
7. The high-temperature resistant PVC tile according to claim 1, characterized in that, The illite has a particle size range of 800-1500 mesh.
8. The high-temperature resistant PVC tile according to claim 1, characterized in that, The crosslinking agent is a mixture of diethylpropylbenzene peroxide and triallyl isocyanurate in a mass ratio of 2:
1.
9. The high-temperature resistant PVC tile according to claim 1, characterized in that, The antioxidant is one or a mixture of antioxidant 1010 and antioxidant 168.
10. A method for preparing PVC roofing sheets, characterized in that, Includes the following steps: (1) Weigh each raw material component according to the weight parts, mix the reinforcing agent and calcium carbonate evenly to obtain the pre-doped filler; (2). The pre-doped filler and other raw materials are transferred to an extruder and heated and extruded to obtain PVC plasticized sheets; (3) PVC plasticized sheets are heated and shaped in a mold, cooled, and cut to obtain PVC tiles.
